The species, density, and intra-plant distribution of mites on red raspberry (Rubus idaeus L.) - Tan, Jiunn Luh; Trandem, Nina; Hamborg, Zhibo; Sapkota, Bijaya; Blystad, Dag-Ragnar; Fránová, Jana; Zemek, Rostislav (Experimental & applied acarology, 2024)
The adoption of the European Green Deal will limit acaricide use in high value crops like raspberry, to be replaced by biological control and other alternative strategies. More basic knowledge on mites in such crops is then necessary, like species, density, and their role as vectors of plant diseases. This study had four aims, focusing on raspberry leaves at northern altitude: (1) identify mite species; (2) study mite population densities; (3) investigate mite intra-plant distribution; (4) investigate co-occurrence of phytophagous mites, raspberry leaf blotch disorder and raspberry leaf blotch virus (RLBV). Four sites in south-eastern Norway were sampled five times. Floricanes from different parts of the sites were collected, taking one leaf from each of the upper, middle, and bottom zones of the cane. Mites were extracted with a washing technique and processed for species identification and RLBV detection. Mites and leaves were tested for RLBV by reverse transcription polymerase chain reaction (RT-PCR) with virus-specific primers. Phytophagous mites, Phyllocoptes gracilis, Tetranychus urticae, and Neotetranychus rubi, and predatory mites, Anystis baccarum and Typhlodromus (Typhlodromus) pyri were identified. All phytophagous mites in cultivated raspberry preferred the upper zone of floricanes, while in non-cultivated raspberry, they preferred the middle zone. The presence of phytophagous mites did not lead to raspberry leaf blotch disorder during this study. RLBV was detected in 1.3% of the sampled plants, none of them with leaf blotch symptoms, and in 4.3% of P. gracilis samples, and in some spider mite samples, implying that Tetranychids could also be vectors of RLBV.
Keywords: Population Density; Animals; nemoci rostlin; roztoči; listy rostlin; Generalist predatory mites; Eriophyidae; Plant Leaves; hustota populace; Norway; Animal Distribution; Norsko; Rubus; Tetranychidae; Raspberry leaf blotch virus; Anystidae; Plant Diseases; Emaravirus idaeobati; zvířata; rozšíření zvířat; Mites